2016
DOI: 10.1093/jac/dkw431
|View full text |Cite
|
Sign up to set email alerts
|

MRSA infections among patients in the emergency department: a European multicentre study

Abstract: This original prospective multicentre study highlights stark differences in European MRSA epidemiology compared with the USA, and that the USA300 CA-MRSA clone is not predominant among community-infected patients in Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 14 publications
4
36
0
Order By: Relevance
“…Thus, there is an urgent need for new drugs specific for MRSA infections. USA300, a representative MRSA strain (van der Mee-Marquet et al 2015;Bouchiat et al 2017;Immergluck et al 2017), was chosen as the strain of interest in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is an urgent need for new drugs specific for MRSA infections. USA300, a representative MRSA strain (van der Mee-Marquet et al 2015;Bouchiat et al 2017;Immergluck et al 2017), was chosen as the strain of interest in this study.…”
Section: Introductionmentioning
confidence: 99%
“…22 Some studies have reported high rates of MRSA in SSSI or similar infections, both CA-MRSA and HA-MRSA, ranging from 22.4% to 74.8%, 1,12 but with important geographic variations. 23 In Portugal CA-MRSA has already been reported, 24 but HA-MRSA clearly predominates.…”
Section: Discussionmentioning
confidence: 99%
“…A striking feature of these CA-MRSA clones was their emergence and spread in the community and their high epidemic success, notably that of the ST80 clone in North Africa, 7 Greece, 8,9 and the middle Est 10 and that of the USA300 clone in the American continent. 11 Knowledge on the underlying driving forces that rule the expansion of these clones is still limited; several non-exclusive contributing factors could be at play.…”
Section: Introductionmentioning
confidence: 99%